JAMMING DESIGNING OF GSM AND CDMA SIGNAL - Joseph Bryan R; Nachrowie Nachrowie; Aries Boedi Setiawan; Sanditiya Kristian S; Dinar Hana S. W (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Jammer is a tool used to transmit signals at the same frequency, so the noise completely submerges the original signal in it. This system works when the device is placed in the jam’s area which wants to be. Thus the device will disturb the transport of information from the sender to the recipient. This device is also useful on facing the war of electronic devices if it is developed in the military environment. The rate enhancement of mobile user can issue some problems at certain place, for insrance worship, lecture halls, libraries, concert halls, conference rooms, etc in daily life. Hence it need to be disabled as mobile phone rings will annoy those places. Jammer is used to interfere with GSM and CDMA operator signals by using square waves and triangular waves, then VCO combines them to produce the interference signals. Then RF transmitters will amplify it to jam the cell phone signals latter.